Respuesta :

ANSWER

[tex]k = 17[/tex]

EXPLANATION

The given function is

[tex]f(x) = 2x + 3[/tex]

The translation that shifts this function 10 units to the right is

[tex]f(x - 10)[/tex]

This implies that

[tex]f(x - 10) = 2(x - 10) + 3[/tex]

We expand the parenthesis to get:

[tex]f(x - 10) = 2x -20+ 3[/tex]

[tex]f(x - 10) = 2x - 17[/tex]

Comparing this equation with

[tex]f(x) = 2x - k[/tex]

we have

[tex]k = 17[/tex]

k=17

The new function would be f(x)=2x-17

In the previous function when u put x=0 you got 3.

Now when the function moves 10 units to the right you still have to get y=3 for x=10. So

2x-k=3 substitute 10 for x

20-k=3 solve for k

K=17.